Unexpected consequences of reintroductions: competition between reintroduced red deer and Apennine chamois. (13th May 2014) - Lovari, S.; Ferretti, F.; Corazza, M.; Minder, I.; Troiani, N.; Ferrari, C.; Saddi, A.
Abstract Reintroductions are commonly used to restore the local biological diversity and/or save threatened taxa. In human‐altered landscapes, we may expect that reintroduced species affect taxa already present. In Abruzzo, Lazio and Molise National Park (central Apennines, Italy), a 30% decline in the abundance of 'vulnerable' Apennine chamois (2005: c. 650 individuals, 2010: c. 450 individuals) has been recorded, whereas red deer (reintroduced in 1972–1987: 81 individuals) have greatly increased (2010: > 2500 individuals). We investigated space and diet overlaps between red deer and Apennine chamois, and their effects on foraging behaviour of the latter. We also compared the composition of grasslands with that recorded when the former were absent. In 2010–2011, we found out: (1) a great space (> 75%) and diet (> 90%) overlap between deer and chamois; (2) a significant increase of unpalatable plant species and a decreasing trend of the nutritious, most grazed species by chamois, in respect to when deer were absent; (3) irrespective from vegetation type, a significantly reduced bite rate of adult female chamois in patches used also by deer, compared with areas without deer. Our results suggest a negative effect of red deer on the availability of nutritious plant species in summer–autumn, possibly because of grazing and physical damage on the grassland caused by trampling. Environmental conditions and access to high‐quality forage in the warm season influence the winter survival of offspring of mountain ungulates. Our results indicate that interspecific overlap in resource use with an increasing, reintroduced population can threaten rare taxa. Reintroductions of potentially competing species should be avoided in areas where populations of threatened taxa exist.